Menopausal metabolic syndrome after hysterectomy - V. I. Podzolkov; L. G. Mozharova; Yu. V. Khomitskaya (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study indapamide retard 1,5 mg effects in women with menopausal metabolic syndrome (MMS) after hysterectomy. Material and methods. The study involved 25 women (mean age 43.82±4.08 years), who underwent subtotal hysterectomy, with one or two ovaries intact, and suffered from Stage I-II arterial hypertension for 2-5 years. In all participants, 24-hour blood pressure (BP) monitoring, the assessment of central hemodynamics, plasma electrolytes and metabolites were performed. The treatment with indapamide retard 1,5 mg lasted for 16 weeks. Results. During the treatment, BP levels significantly decreased: for 24-hour systolic BP (SBP) - by 7.9%, for 24-hour diastolic BP (DBP) – by 9.5%; for daytime SBP and DBP – by 9,5% and 10.8%, respectively; for nighttime SBP and DBP – by 8.9% and 9.0%, respectively. Mostly due to positive dynamics in «overdipper» group, 24-hour BP profile had improved. Stroke and cardiac indices, total peripheral vascular resistance did decrease, with heart rate unchanged. Indapamide retard 1,5 mg did not significantly affect plasma levels of electrolytes, glucose, total cholesterol, uric acid, and immunoreactive insulin. Triglycerides and C-peptide levels declined by 24.68% and 41.59%, respectively. Conclusion. The study confirmed antihypertensive efficacy of indapamide retard 1,5 mg and its beneficial influence of central hemodynamics. Metabolic and electrolytic neutrality gives an opportunity to use indapamide for arterial hypertension management in MMS women.